2014
DOI: 10.4049/jimmunol.1203310
|View full text |Cite
|
Sign up to set email alerts
|

A TNF-α–CCL20–CCR6 Axis Regulates Nod1-Induced B Cell Responses

Abstract: Innate immune responses provoke the accumulation of leukocytes at sites of inflammation. In addition to monocytes and granulocytes, B cells also participate in antimicrobial innate immune responses; however, the mechanisms for accumulation of B cells to sites of inflammation are not well understood. To study B cell accumulation following systemic inflammation, we used a model synthetic ligand that stimulates a specific pattern recognition molecule, nucleotide-binding oligomerization domain–containing protein 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 63 publications
0
18
1
Order By: Relevance
“…Various chemokines have a critical role in B-cell trafficking, both in inflammation and in steady state. 24,25 The CXCR4-CXCL12 axis is particularly important in controlling B-cell homing to and from the bone marrow. 4 It was previously demonstrated that CXCL12 message within the bone marrow decreases 3 days after IFA treatment and this contributed to the loss of bone marrow B cells.…”
Section: Inflammation Enhances B-cell Sensitivity To Cxcl12mentioning
confidence: 99%
“…Various chemokines have a critical role in B-cell trafficking, both in inflammation and in steady state. 24,25 The CXCR4-CXCL12 axis is particularly important in controlling B-cell homing to and from the bone marrow. 4 It was previously demonstrated that CXCL12 message within the bone marrow decreases 3 days after IFA treatment and this contributed to the loss of bone marrow B cells.…”
Section: Inflammation Enhances B-cell Sensitivity To Cxcl12mentioning
confidence: 99%
“…Mature B cells are classified as follicular and marginal zone B cells. Different B cell population were defined as follows, Marginal zone (MZ) B cells as B220 + CD21 hi CD23 int/low , Follicular (FO) B cells as B220 + CD21 int CD23 hi and immature transitional 1 (im/T1) B cells as B220 + CD21 − CD23 − [5A] [15–18]. The mean percentage of immature B cells in mice infected with Msmeg‐pVV16 was found to be 16.57% in contrast to 26.14% in the Msmeg‐PPE18 group.…”
Section: Resultsmentioning
confidence: 99%
“…CCR6+ B cells have recently been shown to enter inflamed skin in which CCL20 is expressed, suggesting a key role for local host defense mechanisms [Paradis et al, ]. In addition, CCR6 deficiency has been shown to cause reduced intestinal IgA responses to oral Ag [Xu et al, ] resulting from alterations in intestinal tissue formation owing to abnormal responses to microbial Ag [McDonald et al, ].…”
Section: Discussionmentioning
confidence: 99%